A Theory of Income and Dividend Smoothing Based on Incumbency Rents - Fudenberg, Drew; Tirole, Jean (Journal of Political Economy, 1995)
"Income smoothing" is the process of manipulating the time profile of earnings or earnings reports to make the reported income stream less variable. This paper builds a theory of income smoothing based on the managers' concern about keeping their position or avoiding interference, and on the idea that current performance receives more weight than past performance when one is assessing the future. When investment is added to the model, so that income reports and dividends can be set independently, we find that both dividends and income reports may be smoothed and that dividends may convey information not present in the income report.